Production of N-acyl homoserine lactones by Chromobacterium haemolyticum KM2 isolated from the river water in Malaysia - Priya, Kumutha; Sulaiman, Joanita; How, Kah Yan; Yin, Wai Fong; Chan, Kok Gan (Springer, 2018)
Quorum sensing (QS) is a term used to describe cell-to-cell communication that enables bacteria to orchestrate group behaviours according to density of bacterial cells. In Gram-negative bacteria, this signalling system is widely known to regulate a variety of different phenotypes such as antibiotic production and biofilm formation. In this study, we report the production of N-acyl homoserine lactones produced by Chromobacterium haemolyticum strain KM2, a bacterium isolated from a river water of a reserved tropical national park. Preliminary screening of QS activity using biosensor reporter assays indicated that C. haemolyticum strain KM2 produces both short- and long-chain AHLs. Analysis with high-resolution liquid chromatography–mass spectrometry (LC–MS/MS) analysis revealed the production of three AHLs by strain KM2: N-octanoyl-l-homoserine lactone (C8-HSL), N-dodecanoyl-l-homoserine lactone (C12-HSL), and N-3-oxo-dodecanoyl-l-homoserine lactone (OC12-HSL). This bacterial isolate also exhibited strong β-haemolytic activity. To the best of our knowledge, this is the first documentation of QS activity and multiple AHLs production by C. haemolyticum strain KM2.